The Substance of Helen and Her Double: The Artistic Drifts of a Myth (Itinera, 2015)
The paper reconsiders some aspects of the ancient legend of Helen, paying particular attention to her divine origin continued in the Spartan and Laconian traditions, which were collected and elaborated by the poet Stesichorus in two different versions of his Palinodia. Here he said that Proteus kept Helen in Aegypt giving to Paris / Alexander an eidôlon of Helen in her substitution. The author wonders about the matter of this eidôlon. The ‘drift’ of this myth is then considered in relationship with the history of visual arts, that seems to have been influenced by the fame of Helen’s beauty from Parrasios and Zeuxis’s time until modern age, in strict connections with its literary afterlife.